1996
DOI: 10.1021/bi952294k
|View full text |Cite
|
Sign up to set email alerts
|

Factor XIIIa-Catalyzed Cross-Linking of Recombinant αC Fragments of Human Fibrinogen

Abstract: Direct measurements of the structure and function of the COOH-terminal portion of the A alpha chain (residues 220-610) of human fibrinogen have been hampered by the difficulty of isolating intact fragments derived from this protease-sensitive region. Here, we overcame this problem by expressing two fragments, alpha C45K (A alpha 221-610) and a truncated version of it, alpha C30K (A alpha 368-610), in Escherichia coli. Both proteins were purified to homogeneous state, and their integrity was confirmed at protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(88 citation statements)
references
References 30 publications
3
85
0
Order By: Relevance
“…Studies of the incorporation of primary amines such as fluorescent dansylcadaverine have shown that glutamine residues involved in the cross-linking reaction of the ␣-chain include Gln221, Gln237, Gln328, and Gln366. [58][59][60] Many lysine residues that potentially function as acceptor sites for the transglutaminase reaction have been reported, including Lys208, Lys219, Lys224, Lys418, Lys427, Lys429, Lys446, Lys448, Lys508, Lys539, Lys556, Lys580, Lys583, Lys601, and Lys606. 61,62 The identification of lysine acceptor sites has been based mainly on incorporation studies of different glutamine-containing peptides such as dansyl-⑀-aminocaproyl-AlaGln-Gln-Ile-Val, and the sites that are involved in ␣-chain crosslinking in vivo are not clear.…”
Section: Substrates Of Factor Xiiia and Biological Consequences Of Crmentioning
confidence: 99%
“…Studies of the incorporation of primary amines such as fluorescent dansylcadaverine have shown that glutamine residues involved in the cross-linking reaction of the ␣-chain include Gln221, Gln237, Gln328, and Gln366. [58][59][60] Many lysine residues that potentially function as acceptor sites for the transglutaminase reaction have been reported, including Lys208, Lys219, Lys224, Lys418, Lys427, Lys429, Lys446, Lys448, Lys508, Lys539, Lys556, Lys580, Lys583, Lys601, and Lys606. 61,62 The identification of lysine acceptor sites has been based mainly on incorporation studies of different glutamine-containing peptides such as dansyl-⑀-aminocaproyl-AlaGln-Gln-Ile-Val, and the sites that are involved in ␣-chain crosslinking in vivo are not clear.…”
Section: Substrates Of Factor Xiiia and Biological Consequences Of Crmentioning
confidence: 99%
“…[17][18][19][20] Five known reactive glutamines in the aC region include Q221 (and/or 223), Q237, Q328, and Q366. 16,[21][22][23] FXIIIa also crosslinks a 2 -antiplasmin (a 2 AP), plasmin activator inhibitor 2 (PAI-2), and fibronectin into the fibrin clot network. [24][25][26][27] FXIII(a) and fibrinogen play additional supporting roles in the presence of red blood cells.…”
Section: Introductionmentioning
confidence: 99%
“…40 Several studies have identified specific crosslinking sites in the aC region responsible for lateral aggregation, but little is known about the individual reactive glutamines and the roles played by the surrounding residues. 17,18,20,22,23,41,42 Antibody studies by Procyk et al identified a FXIIIa binding site within aC (242-424) and then narrowed the site more specifically to aC (389-402). 43 Using recombinant aC (233-425), Smith et al demonstrated that the key contact region for FXIII A 2 9 (thrombin-activated) and A 2 B 2 involves aC (371-425) with E396 playing an important role.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] FXIII-A 2 * stabilizes the forming protofibril by introducing cross-links between adjacent g chains. 17 Cleavage of fibrinopeptide B causes the release of the aC from the central E region enabling FXIII-A 2 * to cross-link adjacent glutamine residues on the AaC at positions Q221, Q237, Q328, and Q366, 18 thereby increasing both the mechanical strength of the developing fiber and resistance to fibrinolysis. 19 In addition to cross-linking g and Aa chains for clot stabilization, FXIII-A 2 * has a key role in cross-linking proteins involved in clot formation and fibrinolysis to the fibrin(ogen) aC regions.…”
Section: Introductionmentioning
confidence: 99%